Clinical radiology the essentials - Daffner, Richard H. 1941-; Hartman, Matthew S. (Wolters Kluwer Lippincott Williams & Wilkins Health, 2014)
Covers the topics in introductory radiology courses and emphasizes clinical problem solving. This title offers guidelines for selecting imaging studies in specific clinical situations and takes a systematic approach to imaging interpretation, presenting a review of normal anatomy, technical and pathologic considerations, and diagnostic advice